Konceptframtagning av plasttrådsavrullningsmaskin - Bäcklund Ekvall, Elias; Gustafsson, Emil (My University, 2021)
Bolon was in need of a more efficient machine for unwinding their plastic threads because of recurring downtime and safety deficiencies. After their weaving process they are left with waste material that they want to recycle and use in the backsides of the carpets. To enable the recycling procedure the company needed a machine that unwinds the coils. Through interviews with the client and the operators a requirement specification was made, this requirement specification was then the basis for the upcoming work. The requirement specification was divided into the following subsections: performance, safety, applicability, materials and ergonomics. Through these aspects five concept solutions was made. After this a set of tests was made to enable a valuation of each concept. After the tests an interview with three representatives from Bolon was held, where the different concepts were discussed. This led to a recommendation from Bolon to which concept we should move on with, a recommendation we shared. After a concept where chosen, the work continued with further development starting with the rollers, this because the other parts depended on the shape and mountings of the rollers. After more tests and contact with a company that manufactures rollers, wider rollers than todays were chosen that would be coated with rubber for more friction between threads and rollers. To build up enough friction between rollers and threads a pressure between the two rollers were needed, at the same time as the loading of the machine had to be easy and safe. After consultation with Bolon a company was contacted that are focusing on pneumatic cylinders, and a decision to use pneumatic cylinders was taken. To enable an even spread of threads across the rollers a 3D-printed model of an eventual distributor of threads was made to evaluate the dimensions needed during this process. There was also clear that a second roller was needed to keep the threads in place. When all these components shapes and sizes was set the frame for the whole machine was designed where the working height was lowered, and safety aspects improved. The new machine lowers downtimes and increases the safety of the workers.